Experiences and beliefs of Malawian women who have delivered with a traditional birth attendant. Issue 1 (April 2015) - Ryan, Julia; Hamela, Gloria; Chome, Nelecy; Kabondo, Charity; Hosseinipour, Mina; Tang, Jennifer
Abstract Objective To explore the beliefs and experiences of Malawian women who have delivered with a traditional birth attendant (TBA). Methods In a qualitative study, 20 face-to-face in-depth interviews and three focus group discussions were conducted between February and May 2013. Women aged 18 years or older and who had a history of delivery with a TBA were recruited from three health centers in Lilongwe District. Their responses were independently coded, and content analysis was used to develop themes and subthemes. Results A total of 46 women participated. Most participants cited difficulties relating to transport and/or unsupportive or unavailable husbands as factors that prohibited their delivery at a health facility. Most had not had a specific delivery plan. The participant responses indicated a discordance between knowledge and practices for safe delivery. Conclusion Strategies to decrease deliveries with TBAs should focus on helping women to develop delivery plans to cope with the potential social or situational obstacles of getting to a facility. Women desire health facilities that provide quality care, emotional support, and personalized care during labor and delivery.